The Impact of Social Media on Interpersonal Relationships in the Digital Era - Reza, Ahmad; Ilham, Fajar; Murdiono, Wahyu (Journal Social Civilecial, 2024)
The subject of this research is how social media affects individuals’ close relationships with other people, with an emphasis on digital jealousy, social comparison, issues of misunderstanding between loved ones and companions, companionship, tips and tricks to minimize negative effects, etc. Because content sharing in social media and other digital platforms is part of daily life now, they strongly influence the emotional and behavioral outcomes. This research establishes the link between digital jealousy and purchase behavior to explain how social comparison on social media can create the motivation for material acquisitions as people seek to replicate what they see on social media platforms. In addition, the research explores the implications of how lack of body language in digital communication results in misunderstanding and aggression to online and offline relationships. The results speak clearly of the need for being alert with what one posts and defines the need to set up social media guidelines in order to maintain positive interactions. Telling to the views of participants, free communication and strict selection of received information by means of social networks help to minimize psychological consequences of digital jealousy and to strengthen healthy relations. As such, this research endeavors to further the current body of knowledge by focusing on specific practices which may be employed to effectively address emotional and relational risks associated with social media while gaining a better appreciation of its impact on one’s well-being and behaviors. The work presents a systematic map of the nature of interactions that people have on digital platforms and how the process should be done deliberately.